Cyclooxygenase‐2 inhibitor suppresses tumour progression of prostate cancer bone metastases in nude mice. (14th February 2014) - Garcia, Marta; Velez, Roberto; Romagosa, Cleofé; Majem, Blanca; Pedrola, Núria; Olivan, Mireia; Rigau, Marina; Guiu, Marc; Gomis, Roger R.; Morote, Juan; Reventós, Jaume; Doll, Andreas
Abstract : Objective: To assess whether celecoxib, a selective cyclooxygenase‐2 (COX‐2) inhibitor with anti‐cancer properties, has an inhibitory effect on tumour establishment and progression of prostate cancer (PCa) bone metastases. Materials and Methods: PC‐3 stable luciferase‐expressing cells were injected into male nude mice by intracardiac (i.c.) and intratibial (i.t.) injections, and the effect of celecoxib on bone metastases was then recorded using bioluminescence image analysis. In cases of chemoprevention, mice received 3 mg/kg celecoxib from 1 week before cell implantation until the end of the study, and to test the therapeutic effect, mice received celecoxib 1 week after cell implantation until the end of the study. Tumour tissue samples were histologically examined and COX‐2 expression was quantified at the protein level. Results: Celecoxib significantly decreased cell viability and the proliferation of human PCa cells in vitro in a dose‐dependent manner. Bone metastases were detected after i.c. injection in nude mice. Celecoxib (15 ppm) administered before i.c. injection did not inhibit the cellular metastatic potential, as the numbers of bone metastases were similar in both groups. However, celecoxib did decrease metastatic progression in the osseous environment when cells were injected directly into the tibia ( P < 0.05). At the protein level, COX‐2 expression was significantly decreased in the celecoxib treatment group ( P < 0.01). Conclusion: In a preclinical mice model, celecoxib administered orally at the standard human dose inhibits the progression of established PCa bone metastases.